Women In the Marvel Cinematic Universe - Kučerová, Lucie (Univerzita Pardubice, 2023)
The diploma thesis is dedicated to the depiction of women characters and superheroines in Marvel Cinematic Universe. Feminism and feminist criticism is explained, as well as popular culture and the evolution of superheorines in the genre of comic books, describing the Marvel phenomenon. The paper analyses the depiction of women in Marvel Cinematic Universe and their representation according to gender stereotypes, patriarchal society, binary oppositions or type of women they mirror. To support the feminist criticism, the Male gaze and Bechdel test are a part of the analysis.
Ženy v Marvel Cinematic Universe
Keywords: feminismus; patriarchální společnost; pohlaví; binární protiklady; andělská žena; objektivizace; feminism; patriarchal society; gender; binary oppositions; angel woman; objectification